STUDY ON THE EXISTING OF METAL ELEMENTS NI, PB, CR AND CD IN THE ZEOLITIZATION PRODUCTS OF FLY ASH WITH NAOH SOLUTION - Wibowo, Widajanti; Hermiati, Teti (Jurnal Zeolit Indonesia, 2005)
Directly reuse of fly ash waste from electricity power plant as soil conditioner is often not recommended, because of its content on heavy metals elements. This research studied the existence of metal elements, Ni, Pb, Cr and Cd in the zeolitization products of fly ash produced in PLTU Suralaya. Zeolitization process was conducted hydrothermal using NaOH solutions of 3N and 4N at temperature of 90oC and 120oC and heating time of 12 hours, 24 hours and 48 hours. 10 kinds of zeolite products were identified as a mixture of zeolite Na-PI, Na6(Si10Al6O32).12H2O and zeolite Na Hydroxysodalite, Na6(SiAlO4)6.4H2O, which had cation-exchange capacity much higher than the original fly ash. Metals ions content of Ni, Pb, Cr and Cd in the zeolite products, analyzed by AAS, were found much decrease compared to its content in the fly ash. Further study on leaching of metals ions from the zeolite products with water on pH neutral did not show a significant losses of these metals ions.